Analisis Pemetaan Ruang Terbuka Hijau dari Hasil Citra Landsat 8 Menggunakan Metode NDVI di Kota Malang - ERLINDA DWITA NURLAILY; Lis Diana Mustafa; Putri Elfa Masudia (Politeknik Negeri Malang, 2020)
This study utilizes Landsat 8 satellite imagery using image processing techniques ranging from radiometric correction, image band merging, and image cutting to obtain the area to be analyzed, namely Malang City. To obtain green open space data in the research area, the NDVI method was chosen as the method. The vegetation density is divided into several classes. The image processing results are compared with the results of field tests using google street view to determine whether the results of the analysis are accurate. The results of the analysis obtained were then made a Decision Support System with the SAW method. This study's output was the creation of an android application containing information systems about green open space in Malang City and recommendations for actions for the benefit of green open space management in Malang City. The system created based on the 2020 image analysis resulted in adding green open space needed in 3 sub-districts, namely Klojen District, Sukun District, and Blimbing District. Meanwhile, the data's accuracy in this study amounted to 86% of the overall data analyzed. In 2016 the total area of ??green open space was 17.81%, in 2017, the area of ??green open space was 15.57%, in 2018, there was a significant increase in the area of ??green open space by 27.92%, in 2019 the area of ??green open space was 17.43%, and in 2020, the area of ??green open space is 17.18% of the total area of ??Malang City.